2020
DOI: 10.1109/access.2020.2974295
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Design of a Parallel Robotic System for Lower Limb Rehabilitation

Abstract: This paper presents the design of an innovative robotic system for lower limb post-stroke rehabilitation of bed confined patients during the acute stage of the treatment. To establish the particularities of each targeted joint motion, experimental measurements are performed on healthy subjects. The acquired data is used to determine the operational workspace, namely the limits of the anatomic joints motion for the lower limb. Based on the prescribed operational workspace, an innovative parallel robotic archite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 23 publications
0
17
0
1
Order By: Relevance
“…Exoskeletons have been extensively studied in recent years because they can enhance the athletic ability of humans. According to different structures, the lower-extremity exoskeletons can be divided into rigid exoskeletons [ 1 , 2 , 3 ] and flexible exoskeletons [ 4 , 5 , 6 ]. The mechanism of a rigid exoskeleton is parallel to the human limbs, which is convenient for weight bearing and rehabilitation training.…”
Section: Introductionmentioning
confidence: 99%
“…Exoskeletons have been extensively studied in recent years because they can enhance the athletic ability of humans. According to different structures, the lower-extremity exoskeletons can be divided into rigid exoskeletons [ 1 , 2 , 3 ] and flexible exoskeletons [ 4 , 5 , 6 ]. The mechanism of a rigid exoskeleton is parallel to the human limbs, which is convenient for weight bearing and rehabilitation training.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, research on rehabilitation robotics has progressed from proposing solutions for the clinical field to more portable solutions tailored to the user’s requirements. However, more efforts are still needed in the development of robotic solutions for neurological rehabilitation that are accessible to a large number of patients as outlined in multiple works such as, for example, reported in ( Volpe et al, 2009 ; Loureiro et al, 2011 ; Yamamoto et al, 2014 ; Copilusi et al, 2015 ; Gherman et al, 2019 ; Gonçalves et al, 2019 ; Vaida et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, it has been shown that exoskeleton-based rehabilitation can be used as an alternative to regular manual therapy to improve motor function [19]. Studies on the development of robotic structures for medical rehabilitation of the lower limb and upper limb have been intensively developed in recent years [20][21][22][23][24][25][26][27][28][29][30]. A complex classification, taking into account defining criteria, of robotic devices for upper limb rehabilitation can be found in [31,32], while in [33], a review of the literature investigating upper body kinematics in people without disabilities through optical motion capture can be found.…”
Section: Introductionmentioning
confidence: 99%